Mechanochemical synthesis of erbium borohydride: Polymorphism, thermal decomposition and hydrogen storage - Gennari, Fabiana Cristina (2013)
A new erbium borohydride Er(BH4)3 was synthesized from 3LiBH4 and ErCl3 through mechanochemical processing. This rare-earth metal borohydride presents a primitive cubic structure with a = 10.74(1) Å, which is isostructural with the one previously reported for R(BH4)3 (R = Y, Dy and Gd). During heating Er(BH4)3 exhibits a reversible structural transformation at about 220 C, analogous to that observed for Y(BH4)3. Combination of thermal hydrogen desorption, DSC, XRPD and FTIR measurements allows to determine that thermal decomposition of Er(BH4)3 starts at 230 C and leads to 3.2 wt% of hydrogen release obtaining ErH2, an unknown intermediate compound and ErB4. It was observed that Er(BH4)3 is partially reversible under 6.0 MPa of H2 at 400 C and absorbs about 20% of the total hydrogen capacity obtained experimentally.